MERAJUT MIMPI ANAK SEJAK DINI: DRAMA KOLOSAL SEBAGAI MEDIA EDUKASI NILAI-NILAI POSITIF - Annafi Nurul Ilmi Azizah; Marzuqoh Nabilah Firyal; Rahma Widia Wati; Saffa Maharani; Vitaria Aqatha; Muti’ah Muti’ah; Dewi Andini Nurhayati; Revalya Ananta Zahra (Institut Teknologi dan Bisnis Swadharma, 2025)
This community service aims to educate early childhood about positive values through role-playing activities in the form of a colossal drama entitled “My Ambition, My Dream”. Early childhood is a rapid stage of character development, so it requires a creative approach that is engaging and taps into the emotional aspects. Colossal drama was chosen as an educational medium because it can stimulate imagination, foster self-expression, and serve as an effective means of conveying moral messages. This activity was carried out at Insan Kamil Kartasura Kindergarten. The method used includes Preparation of activities, Initial observation and identification of needs, implementation of drama performance, and Reflection and Evaluation. The positive values instilled include the spirit of achieving goals, cooperation, self-confidence, discipline, and a sense of responsibility. The results of the activity showed that the children were able to understand the messages conveyed in the story. This activity proves that drama can be an effective educational method in instilling positive values in children from an early age.Pengabdian kepada masyarakat ini bertujuan untuk mengedukasi anak usia dini tentang nilai-nilai positif melalui kegiatan seni peran dalam bentuk drama kolosal berjudul